The Role of Organizational Commitment in Mediating The Influence of Employee Engagement on The Performance of Gen-Z Employees PT. Simojoyo Putra Engineering East Cikarang - Annisa, Nenden Nur; Salsabila, Arista (CV ODIS, 2024)
Human resources (HR) are one of the main factors in an organization because human resources act as movers, thinkers, and planners in an organization to achieve goals. Therefore, quality resources are needed to play this crucial role in improving employee and organizational performance. Several factors can influence performance, including employee engagement and organizational commitment. This research aims to test the effect of employee engagement on employee performance, test the effect of employee engagement on employee organizational commitment, test the effect of organizational commitment on employee performance, and test organizational commitment in mediating the effect of employee engagement on the performance of Generation Z employees. The population in this study were employees of PT. Simojoyo Putra Engineering, East Cikarang. The sampling technique in this research used a purposive sampling technique. The data collection instrument uses a questionnaire and answers are assessed using a Likert scale. To determine the accuracy of the measurements and the stability of the questionnaire parameters, a validity and reliability test was first carried out. Data analysis using the SmartPLS 3.0 for Windows tool. The results of the research show that employee engagement has a positive effect on employee organizational commitment, organizational commitment has a positive effect on employee performance, and organizational commitment can mediate employee engagement on employee performance.